Higher-level process theory motors of Strategic Information Systems (SIS) alignment: an exploratory study - McCarthy, John (2013)
The need for IS Strategies to be optimally aligned with business strategies in order to maximize both value for the business and usability of technology has lead to an understandable emphases on strategic IS alignment for both academics and practitioners (Henderson and Venkatraman, 1999; Galliers and Newell, 2003). However, on review of both the IS strategy and alignment literatures, important limits in current understanding were identified. Although there has been an increasing acceptance of IS strategy as more likely to have an emergent (Avgerou, Ciborra and Land, 2004) rather than a planned rational nature (apropos the seminal work of Mintzberg and Waters (1985)), descriptive and theoretical understanding of this emergent nature was lacking. Further gaps in the IS alignment literature were identified. The predominant emphases of alignment research were on the outcomes and causes of alignment with insufficient consideration given to the ongoing processes of alignment. Very strikingly, the roles of the informal organisation in alignment had been hitherto underexplored and although process (and indeed strategic process) theory had attained a level of maturity; application in alignment process research was conspicuously absent. In essence, literature evaluation had identified that there was an insufficient understanding of IS alignment as an emerging strategic process, from both theory and practitioner perspectives. The following research question could therefore be derived: What process theory motors and relationships characterise SIS alignment process?